Joint Forest Management : Emerging Issues - Bahuguna, V. K. (Indian Forester, 1997)
Joint Forest Management is being practiced in many States now and these experiments are throwing up many challenging issues for decision for the policy makers, foresters, administrators, JFM activists and the planners. This paper discusses the philosophy of JFM as complementary to scientific forest management practices and focuses on the emerging issues for joint collaborative action by all groups engaged in promoting peoples participation in natural resource management.